(untitled) (Papeles, 2022)
Introduction: The description of the disease or events that affect the health of populations and their determinants, as a reason for being of epidemiology, is based on epistemological approaches on which the theoretical foundation of this basic science of public health is built, precepts that must be consolidated in writing in order to facilitate discussion and analysis. Thus, the current research is devoted to show the relevant characteristics of the epistemic approaches used in epidemiological studies. Methodology: For this, narrative documentary research was used. Results and discussion: Epidemiological research is dynamic and in continuous evolution in its epistemological approach for the construction of necessary references in the design and planning of health policies, plans and programs, recognizing that qualitative and quantitative approaches are not mutually exclusive, community participation in the study of health problems and in the success of corrective measures is vital. Conclusion: Health problems must be addressed by epidemiology with epistemological approaches that are not mutually exclusive and that are culturally and scientifically sound, without neglecting methodological rigor and discipline.